Challenges of Public Policies for Tourism in Medium-Sized Cities in Europe: The Cases of Lisbon and Porto (Portugal) - Pavel, Fabiana; Romeiro, Patrícia (GOT: Revista de Geografia e Ordenamento do Território, 2023)
Research Purpose: The significant increase in the flow of international tourists in European cities, regardless of their size, is a phenomenon that has become widespread in the last decade, causing new challenges for local public policies. In Portugal, Lisbon and Porto are not alien to this phenomenon. Recent scientific literature has largely addressed the impacts of increased tourist activity, mostly framing them as a neoliberal political-economic response to structural changes in the economy. Less studied has been the evolution of urban tourism policies and how these have responded to contemporary challenges. Given the need to deepen the knowledge of tourism policies at a local scale, the aim here is to analyse local public tourism policies in Portugal, taking the two largest cities – Lisbon and Porto, as case studies. Methodology: The analysis is carried out from a multiscale perspective, with the aim of understanding how local policies are coordinated with those defined at other scales (national and regional) and is based on a critical review of scientific literature and legislation. Findings: This article provides an organised overview of tourism development and its legal regulations. It also emphasises the importance of creating policies that promote sustainable coexistence between tourism and other urban activities, as well as addressing the varying interests and needs of different parties involved. Originality/Value: The paper focus on the evolution of urban tourism policies and the way in which these have been responding to current challenges, responding to the need to deepen the knowledge of tourism policies at a local scale.